The Concept of Behavioral Architecture in Redesign of Budi Mulia 3 Tresna Werdha Sosial Institution Jakarta - Astuti, Retno Fitri; Putri, Isria Miharti Maherni; Andriana, Sella Tri; Prasetyo, Sutrisno Aji; Hetyorini, Hetyorini (Proceeding International Pelita Bangsa, 2023)
Getting old is a natural process that happens to everyone. Elderly are individuals aged over 60 years who have decreased biological, psychological, social and economic functions. The important thing in designing housing for the elderly is comfort and safety for the elderly in terms of architecture. The study of behavioral architecture in residential design for the elderly is an alternative approach to creating comfortable and safe housing. This is because the elderly need more detailed and in-depth observations of their behavior which will later be implemented into building designs, both physical and non-physical, because a comfortable environment will have a positive psychological impact on the occupants. The Budi Mulia 3 Tresna Werdha Social institution in South Jakarta has inadequate buildings such as: small land and buildings, adequate courtyards without a healthy garden for the elderly, inadequate space in the guest house, materials that are hazardous to the elderly, such as the use of glass on the windows of the house which has started to break down, an inadequate kitchen, dirty rooms and a multipurpose room which has been used as a warehouse because it is not feasible. Because of these existing conditions, a redesign of the orphanage is needed to meet the need for comfort and safety for the elderly living in the social institution. The method used in this design includes evaluating the existing conditions by observing the physical and non-physical conditions in the orphanage, including collecting data on the residents of the orphanage including their characteristics and behavior, as well as collecting data on facilities and infrastructure that do not meet the standards and needs of the elderly. The evaluation continued with the re-planning of the building with an emphasis on the behavior of the elderly, then the building was redesigned. With this redesign, it is hoped that the residents of the Budi Mulia 3 Tresna Werdha Social Institution will have a residence that prioritizes comfort and safety based on the behavior of the elderly living in it.